Extent of social capital formation among Dalits through decentralization process in Kerala during IX plan period - Kumar, K. Mohana (2005)
The present paper mainly analyses the concept of social capital; it also attempts to find out whether decentralisation is helpful in creating social capital. The paper also measures the noticeable creation of social capital among Dalits in the context of Peoples Plan Campaign during IX plan period. People's Plan Campagan is generally considered as a large-scale decentralization experiment the first of its kind in the world. The study observs that there exists a definite local level development. The study found that peoples plan was instrumental in creating new social capital. The creation of the additional social capital and the newly gained political awareness necessarily forges a link between social capital formation and state intervention in Kerala. - Reproduced.
Keywords: Decentralization - India - Kerala; Backward classes - India - Kerala; Social capital - India - Kerala; Social capital